Climate Change in South Asia : Further Need for Mitigation and Adaptation - Agarwal, Ruchir; Balasundharam, Vybhavi; Blagrave, Patrick; Cerutti, Eugenio (Washington, D.C. : International Monetary Fund, 2021)
The South Asia region is both a large contributor to climate change and also one of the regions most vulnerable to climate change. This paper provides an overview of the region's vulnerabilities, national committments to mitigate emissions, and national policies to adapt to a changing climate. The paper also discusses policy measures that may be needed to make further progress on both mitigation and adapatation. Our analysis suggests that while substantial progress is being made, there remains scope to adopt a more cohesive strategy to achieve the region's goals-including by improving the monitoring and tracking of adaptation spending, and by laying the groundwork to equitably increase the effective price of carbon while protecting low-income and vulnerable households in the region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate; Global Warming; Natural Disasters and Their Management; Renewable Resources and Conservation